Characterisation of cholinesterase from kidney tissue of Asian seabass (Lates calcarifer) and its inhibition in presence of metal ions - Hayat, N. M.; Ahmad, Siti Aqlima; Shamaan, Nor Aripin; Sabullah, Mohd Khalizan; Abd. Shukor, Mohd. Yunus; Syed, Mohd. Arif; Khalid, Ariff; Abdul Khalil, Khalilah; Dahalan, Farrah Aini (Triveni Enterprises, 2017)
Aim: The chdinesterase (ChE) based inhibition studies from fish were investigated and presented here emerged to be one of thegreat potential biomarkersfor heavy metals monitoring. Methodology: In this study, the capability of ChE extracted from the kidney of Lates calcarifer was assessed for of metal. ChE was purified through ammonium sulphate precipitation and ion exchange chromatography. Results: The piffled enzyme gave 12 fold purification with the recovery of 12.17% with specific activity of 2.889 U mgJ. The Michaelis-Menten constant (K) and V,^ value obtained was 0.1426 mM and 0.0217 pmol irin'mg∗1, respectively. The enzyme has the ability to hydrolyse acetytthiocholine iodde (ATC) at a faster rate compared to other two synthetic su bstra tes , propionylthiocholine iodide (PTC) and butyrylthiocholine iodide (BTC). ChE gave highest activity at 20- 30°C in Tris-HO buffer pH 8.0. The results showed that cholinesterase from L. calcarifer kidney was very sensitive to sensitive to copper and lead after being tested argentum, arsenic, cadmium, chromium, copper, cobalt, mercury, nickel, lead and zinc. Interpretation: The effect of heavy metals studied on the activity of ChE differed from each other. The result of the study can be used as a tool for futher developing a biomarker for the detection of heavy metals in aquatic ecosystems. In addition, the information can also be used for designing a kit, that would give a rapid and accurate result.